2020
DOI: 10.5539/jfr.v9n5p14
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Aqueous Extracts of Justicia Galeopsis Leaves on the Improvement of Hematological Parameters in Anemic Rats

Abstract: Antianemc potential of aqueous of Justicia galeopsis leaves was studied using Wistar Albino rats after induction of anemia by phenylhydrazine hydrochloride. Forty rats (20 male and 20 female) subdivided into five groups of eight rats were used. There was a group as control (not anemic) and four other anemic groups which had received by gavage respectively 1 ml/kg of distilled water, 1 ml/kg of body weight of Vitafer (reference drug commonly used to treat anemia), 100 mg/kg of body weight of extract of J. galeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…However, the aqueous extract of cooked S. torvum berries at the concentration of 6.4 mg/mL resulted in a higher recovery rate on day 15 compared to the reference anaemia drug (95.19% vs 77.12%) (Table 4). Our results are similar to those obtained by Tchogou et al [28] and Loukou et al [18] who observed in their study a higher haemoglobin recovery rate in the batches of rats treated with aqueous extract of Coco nucefera (Arecaceae) and Justicia Galeopsis (Acanthaceae) respectively compared to the control treated with Vitafer. It is known that iron is part of haemoglobin, myoglobin and cytochrome.…”
Section: Effect Of Aqueous Extract Of Cooked S Torvum Berries On Haemoglobin Levelssupporting
confidence: 93%
See 1 more Smart Citation
“…However, the aqueous extract of cooked S. torvum berries at the concentration of 6.4 mg/mL resulted in a higher recovery rate on day 15 compared to the reference anaemia drug (95.19% vs 77.12%) (Table 4). Our results are similar to those obtained by Tchogou et al [28] and Loukou et al [18] who observed in their study a higher haemoglobin recovery rate in the batches of rats treated with aqueous extract of Coco nucefera (Arecaceae) and Justicia Galeopsis (Acanthaceae) respectively compared to the control treated with Vitafer. It is known that iron is part of haemoglobin, myoglobin and cytochrome.…”
Section: Effect Of Aqueous Extract Of Cooked S Torvum Berries On Haemoglobin Levelssupporting
confidence: 93%
“…In addition, the aqueous extract of cooked berries resulted in greater erythrocyte recovery on day 15 at concentrations of 3.2 and 6.4 mg/mL compared to Vitafer (+116.43% and +223.64% vs +100%) (Table 3). These results are broadly similar to those obtained by Loukou et al [18] who showed that administration of 1000 mg/kg/d of Justicia Galeopsis leaf extract cooked for 30 min increased erythrocyte with a recovery of +98.11%. The extract of leaves cooked for 30 min allows a better stimulation of red blood cell synthesis.…”
Section: Effect Of Aqueous Extract Of Cooked S Torvum Berries On Red Blood Cell Count In Ratssupporting
confidence: 91%